Education and Vulnerability : The Role of Schools in Protecting Young Women and Girls from HIV in Southern Africa - Jukes, M.; Simmons, S.; Bundy, D. (2012)
Education has a potentially important role to play in tackling the spread of HIV, but is there evidence that this potential is realized? This analysis combines the results Of previous literature reviews and updates them with the findings of recent randomized controlled trials and a discussion of possible mechanisms for the effect of schooling on vulnerability to HIV infection. There is a growing body of evidence that keeping girls in school reduces their risk of contracting HIV. The relationship between educational attainment and HIV has changed over time, with educational attainment now more likely to be associated with a lower risk of HIV infection than earlier in the epidemic. Educational attainment cannot, however, be isolated from other socioeconomic factors as the cause of HIV risk reduction. The findings of this analysis suggest that the equitable expansion of primary and secondary schooling for girls in southern Africa will help reduce their vulnerability to HIV. Evidence of ineffective HIV prevention education in schools underlines the need for careful evidence-based programme design. Despite the challenges, recent provisional evidence Suggests that highly targeted programmes promoting realistic options for Young adults may lead to safer sexual behaviour. Targeted education programmes have also been successful in changing students' attitudes to people living with HIV and AIDS, which is associated with testing and treatment decisions. This reduction in stigma may be crucial in encouraging the uptake Of Voluntary Counselling and testing, a central strategy in the control of the epidemic. Expansions of carefully designed and evaluated school-based HIV prevention programmes can help to reduce stigma and have the potential to promote safe sexual behaviour. (c) 2008 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins